Silica Nanoparticles for Insect Pest Control - Cáceres, Mariano; Vassena, Claudia V.; Garcerá, M. D.; Santo-Orihuela, Pablo L. (Current Pharmaceutical Design, 2019)
To date, control strategies used against insect pest species are based on synthetic insecticide applications. In addition, the efficacy of these treatments could be decreased due to insecticide resistance in insect populations. Also, the irrational use of chemical control strategies has negative consequences of non-target organisms and threatening human health. Designing nanomaterial for pest insect control is a promising alternative to traditional insecticide formulations. In particular, it has been proven that silica nanoparticles have the potential for molecules delivery, release control improvement and also their toxicity as insecticide alone. In this work, we summarized the state of knowledge on silica nanoparticles (SiNPs) used in pest insect management. Besides, aspects of their synthesis, mode of action, and toxic effects on non-target organisms and environment are reviewed.
Keywords: Silica nanoparticles